Frequency of Acute Kidney Injury in Children Admitted with Acute Diarrhea - Hussain, Saddam; Hassan, Irfana; Raheem, Abdul; Khan, Mir Qutab; Malik, Abdul; Saddam, Muhammad; Qayum, Komal (Indus Journal of Bioscience Research, 2025)
Background: Worldwide, diarrheal disease continues to be a leading cause of pediatric morbidity and mortality, particularly in areas with limited resources. Acute kidney damage (AKI) is a dangerous but avoidable consequence that is frequently brought on by electrolyte imbalance and dehydration from diarrhea. Improving outcomes for children and minimizing long-term kidney impairment require early detection and intervention. Objective: to evaluate related clinical parameters, including the degree of dehydration, length of illness, and laboratory abnormalities, and to ascertain the prevalence of acute kidney damage (AKI) in children admitted with severe diarrhea to a tertiary care hospital in Quetta, Pakistan. Methods: 200 children with acute diarrhea, ages 1 month to 12 years, were enrolled in this six-month observational study. Individuals with congenital urinary tract abnormalities or a history of renal disease were not included. Using the most recent KDIGO criteria, AKI was diagnosed and staged following clinical evaluation and laboratory testing. Results: Acute kidney injury (AKI) occurred in 24% of the 200 children who were admitted with acute diarrhea. In 88% of instances, there was severe or moderate dehydration, and the majority of affected children were younger than five. All individuals with AKI had elevated blood urea nitrogen (BUN), and almost all had elevated serum creatinine. 64.6% of AKI cases had metabolic acidosis and electrolyte abnormalities, especially those involving salt and potassium. 43.8% were in Stage 1, which indicates early but perhaps reversible kidney damage, based on KDIGO staging. Conclusion: AKI was observed in 24% of children with acute diarrhea, which is frequently associated with severe dehydration and delayed treatment. The majority of instances were in the early stages, indicating that they might be reversible with prompt treatment. In order to stop progression and long-term renal impairment, the study emphasizes the importance of early diagnosis, timely rehydration, ORS use, and increased clinical awareness.